Leitura literária para crianças surdas: uma reflexão sobre práticas de mediação - Fachineti, Sid Cinthia Camila (Universidade Federal de São Carlos, 2025)
Reading mediation can be considered a key process for the development of literacy in deaf children. Several authors discuss strategies that favor this mediation, placing the deaf individual as the protagonist of their teaching-learning process. Therefore, this work seeks to identify and analyze possible strategies for reading mediation of literary texts. To this end, a bibliographic research was carried out that addressed this theme, analyzing articles that present these strategies as a fundamental part of the literacy process of deaf children, considering that literary reading incorporates meanings and values social aspects involving the deaf individual based on their own experiences, developing their communication autonomy using two languages – Libras (Brazilian Sign Language) and Portuguese. Based on the analyzed bibliography, we also considered aspects such as teacher training and methodological resources that favor this mediation, reflecting on how these aspects contribute to the integral development of deaf children. The research indicates that the results and contributions of bilingual mediation practices, the use of visual resources, and the presence of mediators proficient in Libras (Brazilian Sign Language) significantly broaden children's understanding and interest in reading. Furthermore, the research reinforces the importance of literary mediation as an inclusive and formative tool, capable of promoting the linguistic, cultural, and emotional development of deaf students.
Literary reading for deaf children: a reflection on mediation practices
Keywords: Mediação de leitura literária; crianças surdas; educação inclusiva; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade